2007
DOI: 10.1111/j.1468-3083.2007.02170.x
|View full text |Cite
|
Sign up to set email alerts
|

Confetti‐like hypopigmentation: a rare complication of common phototherapeutic modality

Abstract: Confetti-like hypopigmentation: a rare complication of common phototherapeutic modalityEditor Hypopigmentation and vitiligo occurring during psoralen and ultraviolet A (PUVA) therapy have been described in the literature. 1,2 Leucoderma punctatum, a confetti-like hypopigmentation, as a distinct entity was first described by Falabela et al. 3 A 21-year-old woman presented with multiple asymptomatic, punctiform, achromic spots of 1-month duration, distributed predominantly on extensor aspect of extremities. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 6 publications
(9 reference statements)
1
17
0
Order By: Relevance
“…The literature contains several case reports of various clinical forms of hypopigmentation appearing during PUVA 6–9,11–14 or, in one case, 10 NB‐UVB. Most of the patients had MF and a smaller number had psoriasis or vitiligo 6–14 . However, the literature specifically on IGH occurring during phototherapy is strikingly sparse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature contains several case reports of various clinical forms of hypopigmentation appearing during PUVA 6–9,11–14 or, in one case, 10 NB‐UVB. Most of the patients had MF and a smaller number had psoriasis or vitiligo 6–14 . However, the literature specifically on IGH occurring during phototherapy is strikingly sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Disorders of hypopigmentation, such as leucoderma, vitiligo and confetti‐like hypopigmentation, have occasionally been reported in association with phototherapy, mostly in patients with MF 6–14 . IGH‐like lesions appearing during phototherapy have been previously reported in only one patient being treated for MF 13 …”
Section: Introductionmentioning
confidence: 99%
“…The mechanism behind hypopigmentation associated with low‐fluence 1,064‐nm QS Nd:YAG laser treatment is not clear, but a similar phenomenon, known as “leucoderma punctata,” has been described in vitiligo treated with topical or oral psoralen followed by ultraviolet (UV)A irradiation or solar ultraviolet light exposure and in psoriasis treated with UVB phototherapy . Histologic studies have revealed patchy loss of melanin pigment in basal keratinocytes and fewer functional melanocytes and melanin granules . The precise pathophysiology of leucoderma punctata has not been fully elucidated, but one widely accepted theory is that the cumulative phototoxic damage to melanocytes and keratinocytes from phototherapy causes it .…”
Section: Discussionmentioning
confidence: 99%
“…Leukoderma punctatum represents a clinical condition presenting as confetti‐like hypopigmented macules described most commonly in women being treated with 8‐methoxypsoralen and sunlight as a UV source for vitiligo but also has been reported with light chamber UV‐A and topical PUVA 13–15 . Park et al reported four cases of generalized leukoderma punctatum after UV‐B phototherapy for psoriasis, while Bhatnagar et al reported a single case of a vitiligo patient who had both UV‐B and PUVA therapy that developed the leukoderma punctatum after the PUVA 16,17 . On histopathologic examination, patchy loss of melanin in the basal layer with decreased number of melanocytes was observed without any other remarkable change in the epidermis.…”
Section: Discussionmentioning
confidence: 99%